2016
DOI: 10.1007/s40291-016-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition in Renal Cell Carcinoma: Implications for Cancer Therapy

Abstract: Epithelial-to-mesenchymal transition (EMT) is a developmentally vital reversible process by which fully differentiated cells lose their epithelial features and acquire a migratory mesenchymal phenotype. EMT contributes to the metastatic potential of tumors. The expression profile and other biological properties of EMT suggest potential targets for cancer therapy, including in renal-cell carcinoma (RCC). The preclinical and clinical results have substantiated the promises that dysregulated elements leading to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 44 publications
2
72
0
1
Order By: Relevance
“…Epithelial-to-mesenchymal transition (EMT) is a reversible process in which cancer cells loss their epithelial features and transform into mesenchymal cells, and is a crucial step in the acquisition of metastatic behavior of tumors [33]. Sarcomatoid transformation, a fact that can be observed in 8–10% of CCRCCs, represents a good example of neoplastic EMT in renal cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is a reversible process in which cancer cells loss their epithelial features and transform into mesenchymal cells, and is a crucial step in the acquisition of metastatic behavior of tumors [33]. Sarcomatoid transformation, a fact that can be observed in 8–10% of CCRCCs, represents a good example of neoplastic EMT in renal cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed that EMT acts a pivotal role in RCC pathogenesis, tumour aggressiveness and therapeutic effect. 35,36 EMT is also correlated with an advanced recurrence risk and poor overall survival in patients with RCC. 37 Moreover, our data demonstrated that LDHC could upregulate the expression of MMP-9.…”
mentioning
confidence: 98%
“…This mechanism is known as epithelial to mesenchymal transition (EMT) (13, 18). In this process, carcinoma cells lose epithelial phenotype and gain mesenchymal feature (19, 20). Recent clinical and preclinical results showed that the disrupted changes leading to EMT can be potential targets of treatment for RCC patients (20).…”
Section: Genetic Alterations In Sarcomatoid Rccmentioning
confidence: 99%
“…In this process, carcinoma cells lose epithelial phenotype and gain mesenchymal feature (19, 20). Recent clinical and preclinical results showed that the disrupted changes leading to EMT can be potential targets of treatment for RCC patients (20). Jiang et al analyzed 12 cases of sarcomatoid RCC using comparative genomic hybridization technique and found that chromosomal gains are less frequent than chromosomal losses.…”
Section: Genetic Alterations In Sarcomatoid Rccmentioning
confidence: 99%